Admissibility of Forensic Evidence in Indian Courts (Indian Internet Journal of Forensic Medicine and Toxicology, 2012)
Scientific evidences are crucial to the fact finder in order to arrive at the logical consequence in deciding large number of issues brought before him/ her. In the present era, they have almost become indispensable to them. Whether scientific evidence is worth believing or not is a key issue which can be encountered by a judge/ jury when ever scientific evidence is put before him? The issue gains much more importance whenever a new/ upcoming scientific principle is to be applied as evidence in the court of law. The Indian Evidence Act, Section 45 describes an expert. However the law is silent on the objective criterions that should be adopted while admitting or rejecting an expert. There is no other law of the land to regulate the admissibility of a forensic evidence and more so in relation to a new/ upcoming scientific principle. However recently in one the apex court (Supreme Court of India) judgment this issues have been deliberated upon following the principles enunciated in the United States of America. Thus, now in a sense they have the legal sanctions to be applied to the Indian scenario.
Keywords: Forensic evidence; Scientific evidence; Court; Admissibility